Effect of salinity on growth of barnyardgrass (Echinochloa crus-galli), horse purslane (Trianthema portulacastrum), junglerice (Echinochloa colona), and rice - Chauhan, Bhagirath S.; Abugho, Seth B.; Amas, Junrey C.; Gregorio, Glenn B. (Cambridge University Press, 2013)
In Asia, a significant area under rice is affected by salinity. Salt stress can affect growth of crops as well as weeds. A study was conducted in a greenhouse to determine the effect of salinity (electrical conductivity [EC] of 1, 6, 12, 18, and 24 dS m−1) on growth of barnyardgrass, horse purslane, junglerice, and rice. Growth variables were analyzed using regression analysis. The tested levels of EC influenced leaf production of barnyardgrass and junglerice but not that of horse purslane. As compared with the control treatment (EC of 1 dS m−1), shoot biomass of barnyardgrass decreased by only 24% at 12 dS m−1, whereas rice biomass declined by 59% at this level of EC. At EC of 24 dS m−1, barnyardgrass still produced 4% of the biomass of the control treatment, whereas rice did not survive at this level of EC. Junglerice shoot biomass decreased by 73% at 18 dS m−1EC compared with the control treatment, whereas rice shoot biomass declined by more than 86% at 18 dS m−1EC. An EC of 10 dS m−1was required to inhibit 50% shoot biomass of rice, whereas the EC to inhibit 50% shoot biomass of barnyardgrass and junglerice was 15 and 13 dS m−1, respectively. Shoot biomass of horse purslane was not influenced by the tested levels of EC. At the highest EC (24 dS m−1), at which rice did not survive, horse purslane shoot biomass was similar to that of the control treatment. In all weed species, data for root biomass showed trends similar to those of shoot biomass. The results of this study suggest that weeds were more tolerant to salt than rice, and horse purslane was the most tolerant species among the weeds.